Organizational Transformation at the Secretariat of the DPRD Takalar - Maryadi Maryadi; Nawir Rahman; Reynilda Reynilda (Jurnal Manajemen Pelayanan Publik, 2023)
Organizational transformation in the Regional Representative Council (DPRD) has a high urgency given its central role in the democratic system and public decision-making. This study aims to examine the organizational transformation of the DPRD of Takalar Regency and to analyze the determinant factors in the organizational transformation of the institution. The method used in this research is descriptive with a qualitative approach. The informants for this study consisted of DPRD secretariats, DPRD members, and political party officials, with a total of 21 informants. This research collects primary data through FGD. The results of the study show that organizational transformation at the DPRD Takalar secretariat is carried out to 1) increase efficiency in policy-making and supervising executive performance through optimizing decision-making processes and improving legislative products; 2) strengthen accountability and transparency in DPRD; and 3) strengthening the relationship between the DPRD and the community. DPRD must be an inclusive forum for public participation and community aspirations. Overall, organizational transformation in the DPRD has a high urgency to improve efficiency, accountability, capacity, and relations with the community. By adopting an approach that focuses on system change, organizational culture, and community involvement, DPRD can become a more responsive, effective institution, and able to respond to the challenges faced by society and the state.